2023
DOI: 10.1007/s00394-023-03193-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations between diet quality, dietary components, and risk of cardiometabolic multimorbidity in older British men

Abstract: Purpose Cardiometabolic multimorbidity (CMM) is a major public health challenge. This study investigated the prospective relationships between diet quality, dietary components, and risk of CMM in older British men. Methods We used data from the British Regional Heart Study of 2873 men aged 60–79 free of myocardial infarction (MI), stroke, and type 2 diabetes (T2D) at baseline. CMM was defined as the coexistence of two or more cardiometabolic diseases, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that CMM not only signi cantly increases the risk of adverse outcomes such as dementia, reduces the quality of life of patients, and results in shorter life expectancy, but also poses a signi cant challenge to the healthcare system [5][6][7][8][9] . In response to this challenge, research on CMM has intensi ed, and the role of nutrients at the level of modi able risk and preventive factors has gained widespread attention [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CMM not only signi cantly increases the risk of adverse outcomes such as dementia, reduces the quality of life of patients, and results in shorter life expectancy, but also poses a signi cant challenge to the healthcare system [5][6][7][8][9] . In response to this challenge, research on CMM has intensi ed, and the role of nutrients at the level of modi able risk and preventive factors has gained widespread attention [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%